2022
DOI: 10.31926/but.fwiafe.2022.15.64.1.10
|View full text |Cite
|
Sign up to set email alerts
|

The Potency of Avocado Seeds (”Persea Americana” Mill.) as a Source of Antioxidant Tea

Abstract: The processing of avocado into avocado juice will produce organic waste, namely avocado skin, and seeds. This potential of organic waste from avocado seeds can be exploited by turning them into tea products. This study employed avocado seed as a source of antioxidants which was made into processed products, namely tea. This research was intended to discover the influence of temperature with avocado seeds on antioxidants as well as the quality of resulting tea products and to determine the best conditions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Among the efforts to reduce the impact of waste, avocado seeds are used as natural dyes on fabrics. Anwar et al, [18] reported the utilization of avocado seeds as antioxidant tea. Another application of avocado seed was studied by Novelina et al, [19] as a mixture of modified cassava flour in cookies production.…”
Section: Introductionmentioning
confidence: 99%
“…Among the efforts to reduce the impact of waste, avocado seeds are used as natural dyes on fabrics. Anwar et al, [18] reported the utilization of avocado seeds as antioxidant tea. Another application of avocado seed was studied by Novelina et al, [19] as a mixture of modified cassava flour in cookies production.…”
Section: Introductionmentioning
confidence: 99%
“…The use of avocado seeds as an adsorbent has been widely carried out. The results of the research of Munawarah et al (2022) andPutra et al (2022) showed that avocado seed activated charcoal has the potential as an adsorbent of Cd 2+ and Pb 2+ ions. The adsorption potential of avocado seed activated charcoal on Cd 2+ and Pb 2+ ions is optimum at concentrations of 0.38 ppm and 4.83 ppm, respectively, with adsorption efficiency of 97.11% and 97.92%, respectively (Munawarah et al, 2022) and 99.34% for Cd 2+ ions and 98.86% for Pb 2+ ions (Rahayu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the research of Munawarah et al (2022) andPutra et al (2022) showed that avocado seed activated charcoal has the potential as an adsorbent of Cd 2+ and Pb 2+ ions. The adsorption potential of avocado seed activated charcoal on Cd 2+ and Pb 2+ ions is optimum at concentrations of 0.38 ppm and 4.83 ppm, respectively, with adsorption efficiency of 97.11% and 97.92%, respectively (Munawarah et al, 2022) and 99.34% for Cd 2+ ions and 98.86% for Pb 2+ ions (Rahayu, 2014). Characterization of avocado seed activated charcoal showed that activation using 5% H2SO4 activator had good characteristics with a water content of 3.68%, ash content of 0.84%, iodine adsorption 385.22 mg/g, and a surface area of 19.62 m 2 /g.…”
Section: Introductionmentioning
confidence: 99%